The Impact of the Sarimukti Landfill's on the Water Quality of the Cipanawuan River - Eka Wardhani; Vamela Gianina Alessandra (Universitas Diponegoro, 2023)
Sarimukti Landfill operations use a controlled landfill system. The Cipanawuan River is affected by the operational impact of this Landfill. This study aims to identify the effect of leachate from the Sarimukti Landfill on the water quality of the Cipanawuan River. The research method calculates water quality status based on the Decree of the State Minister for the Environment No. 115 of 2003 concerning Guidelines for Determining Water Quality Status. River water quality standards are based on Appendix VI of Government Regulation No. 22 of 2021 concerning implementing Environmental Protection and Management. Water quality parameters identified are parameters that exceed quality standards. Based on the water quality status calculation shows a decrease in water quality from upstream to downstream of the river. The downstream part has been heavily polluted, indicating that there is influence from Sarimukti Landfill operations. Based on the research results, Sarimukti's Treatment Plant's flowing quality for TSS, BOD, and COD is needed to meet quality standards. This can affect water quality, and there is a relationship between the influence of Sarimukti Landfill operations on the water quality of the Cipanawuan River, which is near the Landfill.